The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/gim.2014.173
|View full text |Cite
|
Sign up to set email alerts
|

Is there a duty to recontact in light of new genetic technologies? A systematic review of the literature

Abstract: Purpose: With rapid advances in genetic technologies, new genetic information becomes available much faster today than just a few years ago. This has raised questions about whether clinicians have a duty to recontact eligible patients when new genetic information becomes available and, if such duties exist, how they might be implemented in practice. Methods:We report the results of a systematic literature search on the ethical, legal, social (including psychological), and practical issues involved in recontact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 54 publications
(66 reference statements)
3
90
0
Order By: Relevance
“…The offer of an immediate option to manage their prostate cancer risk, albeit with an emerging evidence base, put most men at ease during recontact and led to low cancer stress several months afterward. Consistent with previous research, these results suggest that recontact is justified and acceptable to patients if the information is actionable or bears personal relevance (Carrieri et al,; Dheensa et al, ; Griffin et al, ; Otten et al, ). For participants in this study, recontact, including the option to engage in research‐based PSA screening, represented a course of action with personal relevance.…”
Section: Discussionsupporting
confidence: 87%
“…The offer of an immediate option to manage their prostate cancer risk, albeit with an emerging evidence base, put most men at ease during recontact and led to low cancer stress several months afterward. Consistent with previous research, these results suggest that recontact is justified and acceptable to patients if the information is actionable or bears personal relevance (Carrieri et al,; Dheensa et al, ; Griffin et al, ; Otten et al, ). For participants in this study, recontact, including the option to engage in research‐based PSA screening, represented a course of action with personal relevance.…”
Section: Discussionsupporting
confidence: 87%
“…For all these reasons, as a recent review of the duty to recontact concluded, in the field of clinical genetics, a ‘reasonable degree of care’ has not yet involved a duty to recontact [1]. No legislation, regulation, clinical guidelines or court decision to date imposes a duty to recontact patients to update genetic advice.…”
Section: A Limited Duty To Current Patients For Genetic Updates?mentioning
confidence: 99%
“…As more individuals have their DNA sequenced or tested, physicians are increasingly presented with patient genetic testing or sequence reports. As scientific knowledge about the medical significance of genetic information continues to evolve, many physicians are concerned and uncertain about their long-term obligations to update medical advice and lack clear legal direction on their responsibilities to update and recontact patients in this regard [1]. Some DNA sequencing laboratories and services have taken it upon themselves to update previous variant classifications on an ad hoc basis and send updated analyses directly to the patient’s physician [2,3].…”
mentioning
confidence: 99%
“…Neither statement directly addresses a genetic provider's duty to recontact their patients about updated genetic testing. Furthermore, even though many genetic professionals may desire recontact, regularly recontacting former patients about new genetic information may require an enormous amount of effort, which is not feasible for many genetics clinics (Otten et al, ). In fact, this systematic review of the literature on recontact by Otten at al.…”
Section: Introductionmentioning
confidence: 99%
“…reveals that 75% of articles concerning recontact address the barriers to recontact. Some of the most common counterarguments for imposing a duty to recontact include knowing which specific patients to recontact, the availability of infrastructure for recontacting and the lack of time, money and staff to perform recontacting (Otten et al, ). Additionally, genetics clinics are also faced with the fact that 11.2% of Americans move residence every year (Jewel, ) and may not inform the genetics department of a change of address.…”
Section: Introductionmentioning
confidence: 99%